2013
DOI: 10.1002/cssc.201300737
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Copper‐Decorated Nickel Nanocatalysts Supported on La2O3 for Low‐Temperature Steam Reforming of Ethanol

Abstract: Copper/nickel nanocatalysts with a unique morphology were prepared by thermal reduction of a perovskite LaNix Cu1-x O3 precursor (x=1, 0.9, and 0.7). During thermal reduction, copper was first reduced and reacted with lanthanum to form metastable Cu5 La and Cu13 La. When the thermal reduction temperature was increased, the perovskite decomposed to Ni and La2 O3 , CuLa alloys disappeared, and Cu deposits on Ni nanoparticles were generated, thereby forming Cu/Ni nanocatalysts with hierarchical structures. Nanosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Since Ni 0 crystallites are active species for steam reforming reaction, all the catalysts reduced with H 2 before reaction. , The reducibility of the prepared catalysts was investigated by H 2 -TPR, and the reduction profiles are shown in Figure . The TPR profile of LaNiO 3 (E) showed two main reduction peaks at 375 and 560 °C, and the lower temperature peak with the shoulder at 300 °C is assigned to the reduction of LaNiO 3 to La 4 Ni 3 O 10 , followed by La 2 NiO 4 . , The second peak corresponds to the reduction of La 2 NiO 4 to Ni 0 . , Similar reduction profiles were observed for the catalyst prepared without template (LaNiO 3 ); however, both the reduction peaks are shifted slightly toward lower temperature region. TPR results demonstrated that reduction of nickel in the perovskite structure is difficult at low temperature.…”
Section: Resultssupporting
confidence: 57%
“…Since Ni 0 crystallites are active species for steam reforming reaction, all the catalysts reduced with H 2 before reaction. , The reducibility of the prepared catalysts was investigated by H 2 -TPR, and the reduction profiles are shown in Figure . The TPR profile of LaNiO 3 (E) showed two main reduction peaks at 375 and 560 °C, and the lower temperature peak with the shoulder at 300 °C is assigned to the reduction of LaNiO 3 to La 4 Ni 3 O 10 , followed by La 2 NiO 4 . , The second peak corresponds to the reduction of La 2 NiO 4 to Ni 0 . , Similar reduction profiles were observed for the catalyst prepared without template (LaNiO 3 ); however, both the reduction peaks are shifted slightly toward lower temperature region. TPR results demonstrated that reduction of nickel in the perovskite structure is difficult at low temperature.…”
Section: Resultssupporting
confidence: 57%
“…One of the factors includes partial re-oxidation of the sample in air during the transfer of samples for analysis in the XPS chamber. 41 Furthermore, Force et al and Kondarides et al showed that the existence of strong metal- a Specific surface area by BET analysis. b Total pore volume estimated at P/P 0 = 0.99. c Average pore diameter calculated by Barrett-Joyner-Halenda (BJH) method.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy (XPS) of Cu 2p core level of CuO NWs/CF was presented in Fig. 2g , where two peaks located at 934.2 and 954.2 eV can be assigned to the binding energy of Cu 2p 3/2 and Cu 2p 1/2 respectively, indicating the presence of the Cu 2+ on the sample 33 34 . In addition, two extra shake-up satellite peaks for Cu 2p 3/2 and Cu 2p 1/2 at 942.1 and 962.2 eV were also observed at higher binding energy side, implying the presence of an unfilled Cu 3d 9 shell and thus further confirming the existence of Cu 2+ on the sample surface.…”
Section: Resultsmentioning
confidence: 99%